MENAKAR PERAN PESANTREN DALAM MENGEMBANGKAN PENDIDIKAN TINGGI MENGHADAPI ERA GLOBALISASI - S. Ali Jadid al Idrus (Universitas Islam Negeri (UIN) Mataram, 2016)
Pesantren (Islamic Boarding Schools) are expected to be institutions that could lead their students to be main actors of current global era. Their students are nowadays expected to be able to integrated sciences, technology, art, life value and environment in developing society. Pesantren are also looked forward to transform themselves into institutions that not only focus on teaching religious materials but also focus on sciences, technology and informatics retaining Islamic values both in its process and its contents so that their outcomes are not only to be Islamic scholars but also scientists. Therefore, the development of higher education in Pesantren should promote integrated studies in order to build superior individuals having a strong competitiveness.